2018
DOI: 10.31219/osf.io/8mtsz
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

English Resumptive Pronouns are More Common where Gaps are Less Acceptable

Abstract: English resumptive pronouns, as in "...the flowers that I don't know where IT came from," are enigmatic in that they are judged to be unacceptable, which would indicate that they are ungrammatical, but are regularly produced by native speakers, which is typically taken to indicate grammaticality. We report results from two studies: an acceptability judgment study on sentences with resumptive pronouns or gaps ("...the flowers that I don't know where _came from"), and a written production study which elicited s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 6 publications
2
16
0
Order By: Relevance
“…It is well known that English speakers produce resumptive pronouns inside islands to 'rescue' ill-formed sentences (e.g. Morgan and Wagers, 2018;Ross, 1967). Importantly, English speakers produce resumptives in precisely the locations where Norwegian would allow gaps.…”
Section: Evidence Of Differencementioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that English speakers produce resumptive pronouns inside islands to 'rescue' ill-formed sentences (e.g. Morgan and Wagers, 2018;Ross, 1967). Importantly, English speakers produce resumptives in precisely the locations where Norwegian would allow gaps.…”
Section: Evidence Of Differencementioning
confidence: 99%
“…. the sale of the uranium that nobody knows what it means' -Donald Trump (Gore et al, 2016, cited in Morgan andWagers, 2018: 861) c. 'Maybe it was a bad idea to get people together and try to record audio with some equipment that we didn't know how it worked.' (CBC Podcast Personal Best, Episode: 'Know more, Carry Less', ~9:00)…”
Section: Evidence Of Differencementioning
confidence: 99%
“…One such strategy is the use of resumptive pronouns (RPs) (Ariel, 1990(Ariel, , 1999 instead of gaps, as demonstrated in ( 11 It has long been observed that when English speakers produce filler-gap dependencies which span syntactic configurations known as islands, rendering an ungrammatical utterance, they sometimes produce a pronoun in the embedded argument position instead of leaving a gap (Alexopoulou & Keller, 2007;F. Ferreira & Swets, 2005;McCloskey, 2017;Morgan & Wagers, 2018;Polinsky, Clemens, Morgan, Xiang, & Heestand, 2013;Ross, 1967;Sells, 1984, among others). In English, this dependency formation technique is categorized as 'intrusive resumption' (McCloskey, 2006) that is, not a part of the grammar.…”
Section: Experiments 2: Restrictiveness and Resumption In Hebrewmentioning
confidence: 99%
“…In English, this dependency formation technique is categorized as 'intrusive resumption' (McCloskey, 2006) that is, not a part of the grammar. Accordingly, it is often viewed as related to the processing of these constructions (Alexopoulou & Keller, 2007;Asudeh, 2004;Dickey, 1996;Erteschik-Shir, 1992;Hawkins, 1999Hawkins, , 2003Morgan & Wagers, 2018; among others).…”
Section: Experiments 2: Restrictiveness and Resumption In Hebrewmentioning
confidence: 99%
“… 3 See Morgan and Wagers (2018) for a recent discussion of how acceptability and production of RPs are connected in RRCs.…”
mentioning
confidence: 99%